2022
DOI: 10.1186/s13104-021-05896-y
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery velocity time integral and corrected flow time measured by a wearable Doppler ultrasound detect stroke volume rise from simulated hemorrhage to transfusion

Abstract: Objective Doppler ultrasonography of the common carotid artery is used to infer stroke volume change and a wearable Doppler ultrasound has been designed to improve this workflow. Previously, in a human model of hemorrhage and resuscitation comprising approximately 50,000 cardiac cycles, we found a strong, linear correlation between changing stroke volume, and measures from the carotid Doppler signal, however, optimal Doppler thresholds for detecting a 10% stroke volume change were not reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…For instance, in the investigation by Barjaktarevic et al a + 4 ms absolute ccFT ∆ was as accurate as + 7 ms, however, + 4 ms traded improved sensitivity for specificity. Further, in previous research on healthy volunteers performing a simple preload modifying maneuver [ 20 ] or undergoing moderate-to-severe central hypovolemia and simulated blood transfusion [ 21 , 31 ], we found that 2% and 4% ccFT ∆ , respectively, best identified a 10% SV ∆ . Hence, we studied these thresholds as well.…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…For instance, in the investigation by Barjaktarevic et al a + 4 ms absolute ccFT ∆ was as accurate as + 7 ms, however, + 4 ms traded improved sensitivity for specificity. Further, in previous research on healthy volunteers performing a simple preload modifying maneuver [ 20 ] or undergoing moderate-to-severe central hypovolemia and simulated blood transfusion [ 21 , 31 ], we found that 2% and 4% ccFT ∆ , respectively, best identified a 10% SV ∆ . Hence, we studied these thresholds as well.…”
Section: Methodssupporting
confidence: 54%
“…Furthermore, ccFT is a promising surrogate for % SV ∆ [ 35 – 43 ], even in the critically ill [ 22 , 44 ], as mentioned in a recent systematic review [ 45 ]. Further, our data in healthy volunteers undergoing moderate-to-severe central hypovolemia, followed by simulated blood transfusion—induced by lower body negative pressure (LBNP) and release—demonstrated a strong, linear relationship between SV ∆ and ccFT ∆ [ 21 , 31 ]. This LBNP analysis comprised approximately 50,000 cardiac cycles making it, to our knowledge, the largest known physiological comparison between SV ∆ and ccFT ∆ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A final implication of this novel framework is that emerging technology may help automate ultrasonographic assessments of both preload (e.g., venous Doppler) and stroke volume (e.g., arterial Doppler), simultaneously ( Figure 4 ) [ 97 ]. We have developed a wireless, wearable Doppler ultrasound that concurrently insonates the jugular vein and common carotid artery [ 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. To our knowledge, we have first reported synchronous venous and arterial Doppler during a dynamic assessment, both in a volume-responsive, healthy volunteer and critically ill, septic patient [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, we recruited 11 healthy adult volunteers 9 , 10 , 12 in a physiology laboratory. Exclusion criteria were known cardiovascular history and/or taking regular cardiovascular medications.…”
Section: Methodsmentioning
confidence: 99%